Factors That Contribute to Success of Start-Ups In Malaysia - Tariko, Vera (2017)
The vast development of start-ups is a trend that can be viewed both globally and on the country level. Some of them do succeed turning into million and billion dollar businesses, but most of them fail. Starting your own business has many challenges and risks, but also brings fulfillment and benefits. There are certain factors that can be found in most successful startups, certain common characteristics, considering which new coming start-ups to a certain level can avoid problems and failure. Not much literature has been found related to the studies of start-ups and factors that contribute to their success, particularly, in Malaysia. In this research, I obtain findings based on several in-depth interviews with key people from the several Malaysian start-ups across various industries, eliciting their valuable insights, opinions and lessons learnt through their journey to sustainability. It is hoped that this research provides valuable insights to both academics and practitioners, on the start-up and start-up ecosystem development in Malaysia.